1962
DOI: 10.1002/aic.690080106
|View full text |Cite
|
Sign up to set email alerts
|

Temperatures and partial pressures at the surfaces of catalyst particles

Abstract: Numerical and graphical methods are presented for estimating the temperatures and partial pressures at the surfaces of catalyst particles for gaseous reactions in flow systems. The errors resulting in the interpretation of catalytic reaction-rate data, where surface conditions are assumed to be those of the ambient gas stream, are presented. A numerical method of evaluating the reaction model with nonisothermal surface conditions is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1963
1963
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(29 citation statements)
references
References 7 publications
1
28
0
Order By: Relevance
“…The experiments in the literature and theoretical calculations (Bizzi et al, 2002) showed that the system operates in a transport-controlled regime. Therefore, the mass-transfer coefficients have to be accounted for in the model, and for this purpose literature expressions have been used (Yoshida et al, 1962) …”
Section: Catalyst Reactivitymentioning
confidence: 99%
“…The experiments in the literature and theoretical calculations (Bizzi et al, 2002) showed that the system operates in a transport-controlled regime. Therefore, the mass-transfer coefficients have to be accounted for in the model, and for this purpose literature expressions have been used (Yoshida et al, 1962) …”
Section: Catalyst Reactivitymentioning
confidence: 99%
“…A specific application may require considerable extrapolation of physical data or reactor geometry. It was pointed out by Hoelscher (8) that these calculations seldom yield values of concentration gradient of significant size; however, examples of larger gradients can be found in the literature (16,25).…”
mentioning
confidence: 98%
“…B e c k (3) hydrogenated ethylene over evaporated h s of nickel, platinum, palladium, and rhodium and found in each case behavior given by Equation (2). As a result some workers (1, 3, 5) have concluded that ethylene hydrogenation involves the reaction of one of the components directly from the gas phase since Equation (1) can be derived on that basis.…”
Section: Workmentioning
confidence: 95%